2017
DOI: 10.1063/1.4975685
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the extent of fast and slow boron-oxygen related degradation in Czochralski silicon by thermal annealing: Evidence of a single defect

Abstract: The fast and slow boron-oxygen related degradation in p-type Czochralski silicon is often attributed to two separate defects due to the different time constants and the determination of different capture cross section ratios (k). However, a recent study using high lifetime samples demonstrated identical recombination properties for the fast and slow degradation and proposed an alternative hypothesis that these were in fact due to a single defect. The study presented in this article provides further experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…[2,6,37] The ratio of electron to hole capture cross sections for the donor level has been found to be in the range between 10 and 20. [6,37] Assuming physically feasible maximum values for σ n and the observed lifetime changes, observation of the responsible SRH center using standard techniques, such as DLTS and MCTS, [10][11][12] should present no difficulty. We have carefully examined the DLTS and MCTS spectra of the Cz-Si:B samples subjected to the LID treatments, and in consistency with the previously published results, Markevich et al [38] have not observed emission signals from deep-level defects, which have been argued to be responsible for the LID.…”
Section: Transitions From the Deep Donor State To Shallow Acceptor St...mentioning
confidence: 99%
See 3 more Smart Citations
“…[2,6,37] The ratio of electron to hole capture cross sections for the donor level has been found to be in the range between 10 and 20. [6,37] Assuming physically feasible maximum values for σ n and the observed lifetime changes, observation of the responsible SRH center using standard techniques, such as DLTS and MCTS, [10][11][12] should present no difficulty. We have carefully examined the DLTS and MCTS spectra of the Cz-Si:B samples subjected to the LID treatments, and in consistency with the previously published results, Markevich et al [38] have not observed emission signals from deep-level defects, which have been argued to be responsible for the LID.…”
Section: Transitions From the Deep Donor State To Shallow Acceptor St...mentioning
confidence: 99%
“…In boron‐doped silicon crystals grown by the Czochralski technique (Cz‐Si), there are two families of defects, which have been known for many years but still lack proper understanding and identification. These are 1) electron traps which were reported by Hornbeck and Haynes in 1955, and 2) defects responsible for light‐induced degradation (LID) of solar cells fabricated from silicon materials containing boron and oxygen atoms …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the present study focused largely on Cu-LID, there are other examples of light-induced defects that are wellunderstood that could be coupled into a similar simulation tool, such as: the boron-oxygen (BO) complex [14,16,[28][29][30][31][32] and Fe-B pair-dissociation [35]. While this approach is not directly applicable to light-induced defects without an established physical root cause, such as the so called Light and Elevated Temperature Induced Degradation (LeTID) [1][2][3], this approach can be used to rule out root causes of unknown LID phenomena, and thus help concentrate research efforts elsewhere.…”
Section: Discussionmentioning
confidence: 99%